Evaluation of direct in liquid spark plasma on disinfection effectiveness and regrowth control of microbial contamination in urban wastewater - A. Barikani; M. Khodadadi; S. Khorami Pour (مجله علوم و فنون هسته‌ای, 2020)
The aim of present study is to evaluate thedisinfection efficiency and regrowth control of microorganism in urban wastewater effluent using cold atmospheric plasma. Two voltages of spark of 20 and 25 kV were applied to wastewater samples of Tehran wastewater treatment plant, Tehran, Iran on 1, 3, and 6 min using oxygen gas supply. The physicochemical characteristics of the effluent sample were determined before and after the treatments. The disinfection efficiency was assessed based on the total colony count and total coliform. The results showed that the COD, BOD5, and the total nitrogen became less than the maximum allowed for agriculture purposes in both treatments, however, this reduction was significantly more in the higher voltage. In terms of bacterial regrowth after disinfection, disinfection efficiency was 100 percent at the beginning of the experiment in all spark treatments, however, total coliform population has become higher than the allowed limit after only one day. This confims the importance of investigating microbial regrowth in wastewater disinfection studies. The spark plasma had no effect on permanent and irreversible inactivation of the total coliform and microbial regrowth occurred.